Perception of 1st year dental students studying in Odisha toward career choice: A cross-sectional survey - Nupur Sharma; Soumik Kabasi; Abhishek Ranjan Pati (Wolters Kluwer Medknow Publications, 2015)
Introduction: There is a growing recognition that the emerging workforce has very different professional expectations to those of earlier generations, with implications for the profession, patients, and the performance of health systems. Aim: To investigate factors that lead to the choice of dentistry as an occupation among the 1st year dental students in three private dental colleges in Bhubaneswar, Odisha, India. Materials and Methods: A cross-sectional survey of 268, 1st year Bachelor of dental surgery students was carried out using a self-administered questionnaire. The questionnaire consisted of total 21 close-ended questions, which included demographic (age and gender) and career choice-related items. Data were collected, analyzed, and was represented as numbers and percentage. Chi-square test was applied for gender wise comparison for the questions pertaining to future plans. The level of significance was set at P < 0.05. Results: A total of 234 duly filled forms were included for the statistical analysis. The majority of respondents were female (n = 158, 67.52%). The extremely important reason for the respondents to choose dentistry as their career choice was that dentistry has more regular hours than other health related professions and would let them make a lot of money (n = 92, 39.31%). This study revealed significant differences between males and females with respect to their perceived future plans. Conclusion: The results of this study highlighted some important influential factors in the choice of dentistry as a professional career.